شهرزاد عند هنري دي رينيه - معمري, ايمان (University of Eloued جامعة الوادي, 2020)
Summary: There is no famous name as SHEHRAZAD is , It is the name that attract attention of the writers east and west , so they start to compose stories and legends about her , And they give her roles they never gave to any woman of all the history of the arts. in fact , The French were the first who draw attention to this great artistic character ,especially after Galan translation of a Thousand and One Nights, This culminated in dozens of literary works that take her as a topic. Henri de Rainier wrote a short story titled” journey of love or the Venetian initiation”, in which the eastern character of Shahrazad is employed in a Western style ,And perhaps what we are interested in in this article is the transition of Eastern Shahrazad to French literature through two stories of this collection:” Sherazade's widowhood.”and” Dialogue between them.”, This study aims to show the extent to which this writer has changed this Eastern myth, After he gave her a greater role than her aesthetic role, where he expresses through it his intellectual and political positions, To become a literary symbol that can speak of the ideas, beliefs and attitudes that he Wandering in his thoughts. He also used to use Sherazade character in different dimensions, Where these stories include topics drawn from history, religion and myth, creating a set of relationships between the characters to play an aesthetic and artistic role. الملخص: ليس هناك اسم يعادل اسم «شهرزاد» شهرةً، فهي التي شغلت الأدباء شرقا وغربا، فراحوا ينسجون حولها القصص والأساطير، ويُلبسونها من الأثواب ما لم يُلبسوه امرأة في تاريخ الآداب كلّها.والحقيقة أنّ الفرنسيين كانوا أوّل من تنبّه إلى هذه الشخصية الفنية العظيمة خاصة بعد ترجمة جالان لكتاب ألف ليلة وليلة ، وقد توّج ذلك بعشرات الأعمال الأدبية التي تتخذ منها موضوعا لها . لقد كتب هنري دي رينييه مجموعة قصصية بعنوان "رحلة حب أو تربية على طريقة أهل البندقية"، موظفا فيها شخصية شهرزاد الشرقية بأسلوب غربي، ولعل ما يهمنا في مقالنا هذا هو انتقال شهرزاد الشرقية إلى الأدب الفرنسي عبر قصتين من هذه المجموعة هما: "ترمل شهرزاد" و"حوار بينهما"، إذ تهدف هذه الدراسة إلى تبيان مدى تغيير هذا الأديب لهذه الأسطورة الشرقية، بعد أن ألقى على عاتقها مهمة أكبر من مهمتها الجمالية، إذ أنه يعبر من خلالها عن مواقفه الفكرية والسياسية، لتصبح رمزا أدبيا يستطيع أن ينطقه بما يجوب في فكره من أفكار ومعتقدات ومواقف. كما كان في توظيفه لشخصية شهرزاد أبعادا مختلفة، إذ تشتمل هذه القصص على موضوعات مستمدة من التاريخ والدين والأسطورة، مشكلا بذلك مجموعة من العلاقات بين الشخصيات لتؤدي دورا جماليا وفنيا.
مقال
Keywords: الكلمات المفتاحية: شهرزاد ، ألف ليلة وليلة، هنري دي رينيه، أدباء فرنسين، أدب مقارن.